Correlation of Clinical Factors with Hypertensive Patient Medication Adherence - Sembiring, Elma Viorentina (Poltekkes Kemenkes Tanjung Karang, 2024)
Hypertension is the primary risk factor for both disability and death worldwide, mainly due to two significant complications: strokes (cerebrovascular accidents) and ischemic heart disease. Hypertension is a condition when systolic blood pressure ≥140mmHg and or diastolic blood pressure ≥90mmHg. Patient adherence is an indicator of the efficacy of therapy. Patient adherence measurement could be done by indirect methods such as self-report and pill count methods. The study aims to determine the correlation between clinical factors and medication adherence in hypertensive patients at Rajabasa Indah Community Health Center. This is a descriptive-analytic study with a cross-sectional approach. Purposive sampling was used in the sampling technique. There are 100 respondents in this study, patients diagnosed with hypertension at Rajabasa Indah Community Health Center who met the inclusion and exclusion criteria. A total of 45 patients were included in the category of non-adherent patients taking medication, and 55 patients were included in the category of patients who adhered to taking medication. This study showed that factors that influenced drug adherence in hypertensive patients were comorbidities (p=0.004), duration of treatment (p=0.007), the number of medications (p=0.002), and history of side effects (p=0.002). Medication adherence has been linked with some clinical factors such as comorbidities, duration of treatment, number of medications, and history of side effects. Incorporating adherence evaluation into the overall assessment of patients undergoing hypertension treatment should be essential.